Development of Adventure-Based Guidance To Improve Self-Management of High School Students - Ambarwati; Farozin, Muh (Universitas Ahmad Dahlan, 2024)
This development study aims to create adventure-based guidance services to enhance students' self-management and to determine the feasibility, practicality, and effectiveness of these services. The development model used is the 4-D model. The selection of subjects was conducted using a random sampling technique. The research subjects consisted of 36 students in the experimental group and 36 students in the control group. The data collection technique involved the use of a questionnaire. Data analysis to determine product effectiveness was conducted using a paired-sample t-test. The results of this study indicate that: (1) The feasibility of adventure-based guidance services, based on validation scores from material experts, falls into the